Deconstructing Islamophobic Discourse: An Impoliteness Theory Approach to Ayad Akhtar's Disgraced - Ahmed, Khalid; Qamar, Syeda Sumera; Tughral, Amna; Khaleel, Badriah; Abdullah, Farhat; Ashraf, Ruqia Saba (Forum for Linguistic Studies, 2025)
This study investigates the exercise of impoliteness strategies in Islamophobic discourse in the play Disgraced. Impoliteness is a multifarious matter that is perhaps apparently, closely related to politeness. It is very much the parasite of politeness. Islamophobia refers to irrational fear, hostility, or prejudice directed against Islam and Muslims, representing a significant barrier to achieving a fair society. The purpose behind this study is to pinpoint the distinctive types of impoliteness strategies used by different characters in the aforesaid play. It further highlights the functions of impolite strategies in an Islamophobic context. Islamophobia is one of the frequently discussed issues in current social scenarios as Muslims constitute a noticeable part of the world and are judged with the lens of prejudice and hatred on the basis of religiosity. It is a qualitative research accomplished by using the latest version of impoliteness model to classify and analyse the facts. The results can be summarized as follows: Among the five strategies of impoliteness—bald on-record impoliteness, positive impoliteness, negative impoliteness, sarcasm, or mock impoliteness—the negative impoliteness strategy emerges as the most frequently employed in this play. The characters in Disgraced frequently employed the affective function.